Surgical Therapy of Cervical Spine Fracture in Patients With Ankylosing Spondylitis. Issue 44 (November 2015) - Unknown
Abstract : Abstract: The present study aimed to explore surgical treatments and assess the effects based on the features of cervical spine fracture in patients with ankylosing spondylitis (AS) and to summarize the experiences in perioperative management. Retrospective analysis was performed in 25 AS patients with cervical spine fracture treated in our hospital from January 2011 to December 2013. The patients were divided according to fracture segments, including 4 cases at C4 to C5, 8 cases at C5 to C6, and 13 cases at C6 to C7. Among them, 12 belonged to I type, 5 to II type, and 8 to III type based on the improved classification method for AS cervical spine fracture. The Subaxial Cervical Spine Injury Classification score for these patients was 7.2 ± 1.3, and the assessment of their neurological function states showed 6 patients (24%) were in American Spinal Injury Association (ASIA) A grade, 1 (4%) in ASIA B grade, 3 (12%) in ASIA C grade, 12 (48%) in ASIA D grade, and 3 (12%) in ASIA E grade. Surgical methods contained simple anterior approach alone, posterior approach alone, and combined posterior–anterior or anterior–posterior approach. The average duration of patients' hospital stay was 38.6 ± 37.6, and the first surgical methods were as follows: anterior approach alone on 6 cases, posterior surgery alone on 9 cases, and combined posterior–anterior or anterior–posterior approach on 10 patients. The median segments of fixation and fusion were 4.1 ± 1.4 sections. Thirteen patients developed complications. During 2 to 36 months of postoperative follow-up, 1 patient died of respiratory failure caused by pulmonary infections 2 months after leaving hospital. At the end of the follow-up, bone graft fusion was achieved in the rest of patients, and obvious looseness or migration of internal fixation was not observed. In addition, the preoperative neurological injury in 12 patients (54.5%) was also alleviated in different levels. AS cervical spine fracture, an unstable fracture, should be treated with operation, and satisfactory effects will be achieved after the individualized surgical treatment according to the improved classification method for AS cervical spine fracture.